Corpo, autonomia e associativismo: a participação das prostitutas da Guaicurus - Juliana Morais de Góes (2017)
Sex workers are among the most vulnerable women in society and, in Brazil, they are mostly black women and with low education. Because of this profile, studies about political behavior would predict that this social group would be less politically active. However, since the 1980s, sex workers organizations have grown and expanded all over Brazil. What has promoted the engagement of these women? What factors make them overcome the difficulties imposed by the situation of vulnerability? The dissertation deals with these issues through a case study about the political participation of the women of the Guaicurus Street (BH/MG), one of the biggest areas of prostitution of the Brazil, with especial attention to the Association of Prostitutes of Minas Gerais - APROSMIG. The first part is a review of the literature about what impact the political participation. The second is a presentation of the story of Guaicurus, the profile of the sex workers interviewed and the participatory pattern of them. To finish, we discuss the factors that contribute to the promotion of the participation of the sex workers and what make them avoid the engagement.